Titanium oxide catalytic membrane as well as preparation method and application thereof

By preparing the titanium oxide catalytic film, the problems of low reaction rates and small suspensions in the prior art were solved, efficient ozone catalysis and the removal of difficult-to-degrade organic matter were achieved, and catalytic performance and ozone utilization were improved.

CN119455943APending Publication Date: 2025-02-18天津大学浙江研究院
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411864541.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the existing catalytic ozone oxidation technology treats difficult-to-degrade organic matter, the reaction rate is low and the small suspended matter affects the subsequent treatment efficiency, and the mass transfer efficiency of the supported metal catalyst is slow, which reduces the catalytic activity.

Method used

Using a titanium oxide catalytic film, the organic solvent is prepared with high-efficiency ozone catalytic properties by stirring components such as pore-making agent powder, titanium precursor solution and iron salt powder in ethanol, and annealing is performed in a muffle furnace. Titanium catalytic film.

Benefits of technology

It improves the utilization rate of ozone and stable catalytic performance, achieves efficient removal of difficult-to-degrade organic pollutants, and assists oxidation and removal through size screening.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455943A_ABST
    Figure CN119455943A_ABST
Patent Text Reader

Abstract

The invention provides a titanium oxide catalytic membrane as well as a preparation method and application thereof, and the method comprises the following steps: dissolving pore-forming agent powder in ethanol, stirring into a uniform solution, adding an acetic acid solution, a titanium precursor solution and ferric salt powder, and vigorously stirring until the solution is clear and transparent to obtain an organic solvent; washing the surface of the ceramic membrane with absolute ethyl alcohol and deionized water, and drying for later use; the ceramic membrane is soaked in an organic solvent for 0-6 h and then transferred to a crucible, the crucible is placed in a muffle furnace, the temperature is increased to 300-800 DEG C firstly, first annealing is conducted for 1-3 h, the temperature is continuously increased to 800-1000 DEG C, second annealing is conducted for 0.5-2 h, and the temperature increasing speed is 5 DEG C / min; and taking out the ceramic membrane in the muffle furnace, washing redundant titanium dioxide powder on the surface with deionized water, and completely drying in a drying oven at 60 DEG C to prepare the titanium oxide catalytic membrane. The titanium oxide catalytic membrane prepared by the invention has the advantages of efficient ozone catalytic performance, improvement of ozone utilization rate, stable performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure belongs to the field of membrane material preparation, and in particular relates to a titanium oxide catalytic membrane, a preparation method and applications thereof. Background Art

[0002] Refractory organic wastewater poses a significant threat to the environment and water bodies. Currently, research reports on methods for degrading organic wastewater include coagulation and sedimentation, microelectrolysis, activated carbon, wet oxidation, catalytic oxidation, and membrane separation. Among these, catalytic ozone oxidation technology has been a hot topic in the water treatment field in recent years. Ozone is an electrophilic oxidant with strong oxidizing power. Leveraging ozone's strong oxidizing properties, solid catalysts are introduced into the reaction system to accelerate its decomposition, converting it into hydroxyl radicals, which are more oxidizing but less selective, thereby increasing the oxidative removal efficiency of organic pollutants. Catalytic ozone oxidation technology offers advantages such as high efficiency in removing refractory organic matter and zero secondary pollution, making it widely used in advanced wastewater treatment. However, it also has certain limitations. Firstly, the low concentration of refractory organic matter results in a slow reaction rate between ozone and pollutants. Secondly, the small suspended solids produced during the catalytic ozone oxidation of refractory organic matter affect the efficiency of subsequent treatment processes.

[0003] Ozone catalysts often use transition metal oxides as active components. Titanium oxide, iron oxide, aluminum oxide, etc. are often used for ozone oxidation. Among them, titanium dioxide is an n-type semiconductor material. Due to its low cost and good catalytic oxidation ability, it has become one of the most widely used catalysts today. However, in heterogeneous catalysis, due to the natural aggregation tendency of metal catalysts, the number of exposed metal sites of supported metal catalysts is small, and the mass transfer efficiency is slow, thereby reducing the catalytic activity in the catalytic ozone oxidation reaction. Ceramic catalytic membranes, by loading the catalyst on ceramic membranes, not only effectively solve the problems of catalyst recovery and agglomeration, but also achieve the synergistic effect of membrane filtration and catalytic ozonation. In addition, the high chemical stability and large specific surface area of ​​ceramic catalytic membranes improve the mass transfer rate of pollutants to the active sites and the catalytic performance of ceramic catalytic membranes in the catalytic oxidation of ozone. Summary of the Invention

[0004] This disclosure provides a titanium oxide catalytic membrane, preparation method, and application thereof. The resulting titanium oxide catalytic membrane exhibits advantages such as efficient ozone catalysis, improved ozone utilization, and stable performance. Organic matter can be efficiently removed by directly reacting with ozone molecules or with hydroxyl radicals generated by catalytic ozone, achieving efficient removal of difficult-to-degrade organic pollutants. The size-screening effect of the catalytic membrane also assists in the oxidation and removal of difficult-to-degrade organic matter.

[0005] According to a first aspect of the present disclosure, a method for preparing a titanium oxide catalytic film is provided, the method comprising:

[0006] The pore-forming agent powder is dissolved in ethanol, stirred to form a uniform solution, and then the acetic acid solution, titanium precursor solution and iron salt powder are added, and stirred vigorously until the solution becomes clear and transparent to obtain an organic solvent;

[0007] Use anhydrous ethanol and deionized water to clean the surface of the ceramic membrane and dry it for later use;

[0008] The ceramic membrane is immersed in the organic solvent for 0-6 hours and then transferred to a crucible. The crucible is placed in a muffle furnace and heated to 300-800°C for a first annealing for 1-3 hours. The temperature is then continuously raised to 800-1000°C for a second annealing for 0.5-2 hours at a heating rate of 5°C / min.

[0009] The ceramic membrane in the muffle furnace was taken out, and the excess titanium dioxide powder on the surface was washed with deionized water. The membrane was placed in an oven at 60° C. and completely dried to prepare a titanium oxide catalytic membrane.

[0010] Furthermore, the pore-forming agent powder is one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyurethane, and hydroxypropyl cellulose.

[0011] Furthermore, the titanium precursor solution can be one or more of tetrabutyl titanate, isopropyl titanate, tetraethyl titanate, tetrabutyl titanate tetramer, di(triethanolamine)diisopropyl titanate, bis(acetylacetonato)diisopropyl titanate, tetraisobutyl orthotitanate, and tetraoctadecyl orthotitanate.

[0012] Furthermore, the iron salt is one or more of ferric acetylacetonate, ferric nitrate nonahydrate, ferric chloride, ferric phosphate, ferric citrate, ammonium ferric citrate, ferrocene, ferric acetate, acetylferrocene, butylferrocene, aminoferrocene, ferric p-toluenesulfonate, ferric pyrophosphate, 1,1'ferrocene, hydroxymethylferrocene, ferric stearate, ferric acetate, 1-hydroxyethylferrocene, ferric trifluoromethanesulfonate, vinylferrocene, ethylferrocene, 1,1'diacetylferrocene, and ferric titanate.

[0013] Furthermore, the volume ratio of the titanium precursor to the ethanol is (2 60): (40 60).

[0014] Furthermore, the molar ratio of the iron salt to the titanium precursor is (1:10):(1:400).

[0015] Furthermore, the ceramic membrane is immersed in the organic solvent for 3 hours.

[0016] Furthermore, the first annealing temperature of the ceramic membrane in the muffle furnace is 600° C., and the annealing time is 2 hours; the second annealing temperature is 800° C., and the annealing time is 1 hour.

[0017] According to a second aspect of the present disclosure, a titanium oxide catalytic membrane is provided, which is prepared by the preparation method according to any one of claims 1 to 8.

[0018] According to a second aspect of the present disclosure, an application of a titanium oxide catalytic membrane is provided. The titanium oxide catalytic membrane is applied in the field of wastewater treatment technology.

[0019] Compared with the prior art, the beneficial effects of the present disclosure are as follows: First, the surface of the titanium oxide catalytic membrane prepared by the present disclosure is rutile, or titanium oxide with rutile as the main phase, which has the advantages of efficient ozone catalytic performance, improved ozone utilization rate and stable performance. Organic matter can achieve efficient removal of difficult-to-degrade organic pollutants by directly reacting with ozone molecules, or reacting with hydroxyl radicals generated by catalytic ozone; at the same time, the size screening effect of the catalytic membrane can also assist in the oxidation and removal of difficult-to-degrade organic matter. Secondly, the preparation method of the titanium oxide catalytic membrane disclosed in the present disclosure has the advantages of simple process, mild preparation conditions, wide application range, reusability and low economic cost, and is easy to scale up and promote.

[0020] It should be understood that the contents described in this section are not intended to identify the key or important features of the embodiments of the present disclosure, nor are they intended to limit the scope of the present disclosure. Other features of the present disclosure will become readily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings, in which several embodiments of the present disclosure are shown by way of example and not limitation, wherein:

[0022] In the drawings, the same or corresponding reference numerals denote the same or corresponding parts.

[0023] Figure 1 It is a schematic flow chart of the method for preparing the titanium oxide catalytic film disclosed in the present invention;

[0024] Figure 2 X-ray diffraction patterns of the catalytic films obtained by the preparation methods of Comparative Example 1 and Examples 1-4 of the present disclosure;

[0025] Figure 3 This is a scanning electron microscope image of the surface of the ceramic membrane obtained by the preparation method of Comparative Example 1 of the present disclosure;

[0026] Figure 4 This is a scanning electron microscope image of the surface of the titanium oxide catalyst film obtained by the preparation method of Example 1 of the present disclosure;

[0027] Figure 5 This is a scanning electron microscope image of the surface of the titanium oxide catalyst film obtained by the preparation method of Example 2 of the present disclosure;

[0028] Figure 6 This is a scanning electron microscope image of the surface of the titanium oxide catalyst film obtained by the preparation method of Example 3 of the present disclosure;

[0029] Figure 7 This is a scanning electron microscope image of the surface of the titanium oxide catalyst film obtained by the preparation method of Example 4 of the present disclosure. DETAILED DESCRIPTION

[0030] To make the purposes, features, and advantages of the present disclosure more apparent and understandable, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present disclosure without creative work shall fall within the scope of protection of the present disclosure.

[0031] There is no particular limitation on the sources of all raw materials in the present disclosure and the following examples, and any raw materials may be commercially available.

[0032] The method for detecting water permeation flux in the embodiment of the present disclosure is as follows:

[0033] A self-built ozone test system was used to test the catalytic oxidation performance of titanium oxide catalytic membrane on organic pollutants. The test system consists of oxygen generator, ozone generator, pipeline, regulating valve, pressure and flow detector and other components. The gas flow rate is 2L / min and the test temperature is 25±0.5℃.

[0034] The catalytic oxidation experiment of organic matter used a solution prepared with atrazine, with an initial concentration of 0.2 mg / L. After adding ozone concentrated water, the effective dissolved ozone concentration was 0.5 mg / L. Then, a membrane filtration experiment was immediately carried out, with a membrane flux of 50 L m 2 h 1 .

[0035] After 20 minutes, samples were taken to test the atrazine concentration and calculate the removal rate.

[0036] Atrazine concentrations were measured using liquid chromatography.

[0037] Comparative Example 1:

[0038] The surface of the ceramic membrane was cleaned with anhydrous ethanol and deionized water, and the surface impurities were removed and then dried to obtain the original ceramic membrane.

[0039] See also Figure 2 The X-ray diffraction pattern of the ceramic membrane obtained by the preparation method of Comparative Example 1 disclosed in the present invention shows a strong characteristic peak at 25° in the XRD spectrum of Comparative Example 1, which is the 012 crystal plane of α-phase alumina, because the original ceramic membrane purchased is an α-phase alumina ceramic membrane. Figure 3 This is a scanning electron microscope image of the surface of the ceramic membrane obtained by the preparation method of Comparative Example 1 of the present disclosure. It can be seen that there is an obvious pore structure on the surface of the ceramic membrane.

[0040] Among them, the removal rate of atrazine by the original ceramic membrane was 8.9%.

[0041] Example 1:

[0042] Take 1g of polyvinyl pyrrolidone and dissolve it in 20ml of anhydrous ethanol. Stir it at 60℃ for two hours until it becomes a transparent liquid. Then add 4ml of acetic acid and stir for 30 minutes. Finally, add 2mL of tetrabutyl titanate (TBOT) containing 104.2mg of ferric acetylacetonate to the above solution and stir for 1h to obtain an orange-red clear solution, which is an organic solvent. The cleaned ceramic membrane is soaked in the organic solvent for 3 hours. After soaking, it is transferred to a 60℃ oven to dry the solvent. The temperature is raised to 600℃ in a muffle furnace for the first annealing for 2 hours, and then the temperature is continued to rise to 800℃ for a second annealing for 1 hour (heating rate is 5℃ / min) to obtain a titanium oxide ceramic membrane, which is recorded as TBOT-2.

[0043] See also Figure 2 From the X-ray diffraction pattern of the titanium oxide catalyst film prepared by the preparation method of Example 1 of the present disclosure, it can be seen that the intensity of the characteristic peak of titanium oxide at 27° is significantly increased and is almost the same as the peak intensity at 25°. Figure 4 This is a scanning electron microscope image of the surface of the titanium oxide catalytic membrane obtained by the preparation method of Example 1 of the present disclosure. It can be seen that the pore structure on the surface of the ceramic membrane is filled with titanium oxide, presenting a dense surface morphology.

[0044] In the detection of water permeation flux, the atrazine removal rate of TBOT-2 ceramic membrane was 68.2%.

[0045] Example 2:

[0046] Take 1g of polyvinyl pyrrolidone and dissolve it in 20ml of anhydrous ethanol. Stir it at 60℃ for two hours until it becomes a transparent liquid. Then add 4ml of acetic acid and stir for 30 minutes. Finally, add 5mL of tetrabutyl titanate containing 259.58mg of ferric acetylacetonate to the above solution and stir for 1h to obtain an orange-red clear solution, which is an organic solvent. The cleaned ceramic membrane is soaked in the organic solvent for 3 hours. After soaking, it is transferred to a 60℃ oven to dry the solvent. The temperature is raised to 600℃ in a muffle furnace for the first annealing for 2 hours, and then the temperature is continued to rise to 800℃ for the second annealing for 1 hour (heating rate is 5℃ / min) to obtain a titanium oxide ceramic membrane, which is recorded as TBOT-5.

[0047] See also Figure 2From the X-ray diffraction pattern of the titanium oxide catalytic film prepared by the preparation method of Example 2 of the present disclosure, it can be seen that the intensity of the characteristic peak of titanium oxide at 27° is higher than that at 25°, indicating that the loading amount of rutile phase titanium oxide is significantly increased. Figure 5 This is a scanning electron microscope image of the surface of the titanium oxide catalytic membrane obtained by the preparation method of Example 2 of the present disclosure. It can be seen that the membrane surface has a dense flaky structure.

[0048] In the detection of water permeation flux, the atrazine removal rate of TBOT-5 ceramic membrane was 73.6%.

[0049] Example 3:

[0050] Take 1g of polyvinyl pyrrolidone and dissolve it in 20ml of anhydrous ethanol. Stir it at 60℃ for two hours until it becomes a transparent liquid. Then add 4ml of acetic acid and stir for 30 minutes. Finally, add 10mL of tetrabutyl titanate containing 518.8mg of ferric acetylacetonate to the above solution and stir for 1h to obtain an orange-red clear solution, which is an organic solvent. The cleaned ceramic membrane is soaked in the organic solvent for 3 hours. After soaking, it is transferred to a 60℃ oven to dry the solvent. The temperature is raised to 600℃ in a muffle furnace for the first annealing for 2 hours, and then the temperature is continued to rise to 800℃ for the second annealing for 1 hour (heating rate is 5℃ / min) to obtain a titanium oxide ceramic membrane, which is recorded as TBOT-10.

[0051] See also Figure 2 From the X-ray diffraction pattern of the titanium oxide catalytic film prepared by the preparation method of Example 3 of the present disclosure, it can be seen that as the content of tetrabutyl titanate and iron acetylacetonate continues to increase, the characteristic peak intensity of rutile phase titanium oxide continues to increase. Figure 6 This is a scanning electron microscope image of the surface of the titanium oxide catalytic membrane obtained by the preparation method of Example 3 of the present disclosure. It can be seen that there is a large amount of powder accumulation on the surface of the membrane, which may be caused by too much titanium oxide loading.

[0052] In the water permeation flux test, the atrazine removal rate of TBOT-10 ceramic membrane was 92.3%.

[0053] Example 4:

[0054] Take 1g of polyvinyl pyrrolidone and dissolve it in 20ml of anhydrous ethanol. Stir it at 60℃ for two hours until it becomes a transparent liquid. Then add 4ml of acetic acid and stir for 30 minutes. Finally, add 20mL of tetrabutyl titanate containing 1.0378g of ferric acetylacetonate to the above solution and stir for 1h to obtain an orange-red clear solution, i.e., an organic solvent. The cleaned ceramic membrane is soaked in the organic solvent for 3 hours. After soaking, it is transferred to a 60℃ oven to dry the solvent. The membrane is heated to 600℃ in a muffle furnace for the first annealing for 2 hours, and then the temperature is continued to rise to 800℃ for the second annealing for 1 hour (heating rate is 5℃ / min) to obtain a titanium oxide ceramic membrane, which is recorded as TBOT-20.

[0055] See also Figure 2 From the X-ray diffraction pattern of the titanium oxide catalytic film obtained by the preparation method of Example 4 of the present disclosure, it can be seen that the characteristic peak of titanium oxide has decreased compared with the previous samples. This may be because the content of tetrabutyl titanate and iron acetylacetonate in the preparation process is too high, which is not conducive to the formation of titanium oxide. Figure 7 This is a scanning electron microscope image of the surface of the titanium oxide catalytic membrane obtained by the preparation method of Example 4 of the present disclosure. It can be seen that there is still excessive titanium oxide accumulation on the membrane surface.

[0056] In the water permeation flux test, the atrazine removal rate of TBOT-20 ceramic membrane was 83.7%.

[0057] Based on the above examples, the titanium oxide catalytic membrane prepared by the present disclosure has the advantages of efficient ozone catalysis, improved ozone utilization, and stable performance. Organic matter can be efficiently removed from difficult-to-degrade organic pollutants by directly reacting with ozone molecules or with hydroxyl radicals generated by catalytic ozone. The size screening effect of the catalytic membrane can also assist in the oxidation and removal of difficult-to-degrade organic matter. The preparation method has the advantages of simple process, mild preparation conditions, wide applicability, reusability, and low economic cost, making it easy to scale up and promote.

[0058] It should be understood that the various forms of the processes shown above can be used to reorder, add, or delete steps. For example, the steps described in this disclosure can be performed in parallel, sequentially, or in a different order, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved. This is not a limitation herein.

[0059] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features being referred to. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one such feature. Throughout the present disclosure, "plurality" means two or more, unless otherwise specifically defined.

[0060] The above description is merely a specific embodiment of the present disclosure, but the scope of protection of the present disclosure is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this disclosure should be included in the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure should be based on the scope of protection of the claims.

Claims

1. A method for preparing a titanium oxide catalyst film, characterized in that: The method comprises: The pore-forming agent powder is dissolved in ethanol, stirred to form a uniform solution, and then the acetic acid solution, the titanium precursor solution and the iron salt powder are added, and stirred vigorously until the solution is clear and transparent to obtain an organic solvent; The surface of the ceramic membrane is cleaned with anhydrous ethanol and deionized water, and dried for later use; After soaking the ceramic film in the organic solvent for 0-6 hours, the film is transferred to a crucible, and the crucible is placed in a muffle furnace, first heated to 300-800° C. for a first annealing for 1-3 hours, and then heated to 800-1000° C. for a second annealing for 0.5-2 hours, with a heating rate of 5° C. / min; The ceramic membrane in the muffle furnace was taken out, and the excess titanium dioxide powder on the surface was washed with deionized water. The membrane was placed in an oven at 60° C. and completely dried to prepare a titanium oxide catalytic membrane.

2. The method according to claim 1, characterized in that The pore-forming agent powder is one or more of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyurethane, and hydroxypropyl cellulose.

3. The method according to claim 1, characterized in that The titanium precursor solution can be one or more of tetrabutyl titanate, isopropyl titanate, tetraethyl titanate, tetrabutyl titanate tetramer, di(triethanolamine) diisopropyl titanate, bis(acetylacetonato) diisopropyl titanate, tetraisobutyl orthotitanate, and tetraoctadecyl orthotitanate.

4. The method according to claim 1, characterized in that The iron salt is one or more of ferric acetylacetonate, ferric nitrate nonahydrate, ferric chloride, ferric phosphate, ferric citrate, ammonium ferric citrate, ferrocene, ferric acetate, acetylferrocene, butylferrocene, aminoferrocene, ferric p-toluenesulfonate, ferric pyrophosphate, 1,1'-ylferrocene, hydroxymethylferrocene, ferric stearate, ferric acetate, 1-hydroxyethylferrocene, ferric trifluoromethanesulfonate, vinylferrocene, ethylferrocene, 1,1'-diacetylferrocene, and ferric titanate.

5. The method according to claim 1, characterized in that The volume ratio of the titanium precursor to the ethanol is (260):(40 60).

6. The method according to claim 1, characterized in that The molar ratio of the iron salt to the titanium precursor is (1:10):(1:400).

7. The method according to claim 1, characterized in that The ceramic membrane is immersed in the organic solvent for 3 hours.

8. The method according to claim 1, characterized in that The first annealing temperature of the ceramic membrane in the muffle furnace is 600° C., and the annealing time is 2 hours; the second annealing temperature is 800° C., and the annealing time is 1 hour.

9. A titanium oxide catalyst film, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 8.

10. The titanium oxide catalytic membrane according to claim 9 is used in the field of wastewater treatment technology.

Citation Information

Cited By

  • Preparation method of metal-based ceramic composite membrane with ozone catalysis function

    CN121623584A